Optimal Design and Governance of Asset-Backed Securities - Riddiough, Timothy J (Journal of Financial Intermediation, 1997)
A model of asymmetric asset value information and nonverifiability of liquidation motives is developed to examine the optimal design and governance of asset-backed securities. Because of adverse selection risk, the liquidation option of whole loan sale results in external price discounting of composite cash flows. The alternative liquidation option of senior/subordinated security design is shown to dominate whole loan sale, since cash flow splitting allows the issuer to internalize some or all of the lemons-related liquidation costs. Security subordination levels must increase relative to full information levels, however, to protect uninformed outside investors. Pool diversification and loan bundling are shown to be packaging strategies that can soften the lemons-related subordination effect and therefore increase liquidation proceeds. With respect to security governance, we show that it is the junior securityholder who should control the debt renegotiation process with pooled debt structures. Better asset value information and a first loss position are the reasons for junior securityholder control in our model. Numerous empirical implications of the model are also identified and discussed.Journal of Economic LiteratureClassification Numbers: D46, D81, D82, G13, G21, G24, G32, G33.